Finite element simulation of head impacts in mixed martial arts. Issue 3 (17th February 2021) - Tiernan, Stephen; Meagher, Aidan; O'Sullivan, David; O'Kelly, Eoin
Abstract: Thirteen MMA athletes were fitted with the MiG2.0 Stanford instrumented mouthguard. 451 video confirmed impacts were recoded during sparring sessions and competitive events. The competitive events resulted in five concussions. The impact with the highest angular acceleration from each event was simulated using the GHBMC head model. Average strain in the corpus callosum of concussed fighters was 0.27, which was 87.9% higher than uninjured fighters and was the best strain indicator of concussion. The best overall predictor of concussion found in this study was shear stress in the corpus callosum which differed by 111.4% between concussed and uninjured athletes.